PERLINDUNGAN TERHADAP POTENSI PELANGGARAN HUKUM PADA PENGGUNAAN APLIKASI FOTOYU - NIM. A1012221091, FATHURRAHMAN (Fakultas Hukum Universitas Tanjungpura, 2026)
Abstract The phenomenon of digital transactions in the FOTOYU application as a platform for buying and selling photos and videos has the potential to lead to violations related to copyright infringement, misuse of personal data, and the use of works without permission. This condition reflects violations of consumer rights and photographers' copyrights. The purpose of this study is to analyze the forms of violations as well as the forms of protection against these violations on the FOTOYU application. This research uses a normative legal method with a descriptive approach. Data is obtained through literature research and the application of legal norms in accordance with legislation. The collected data is then analyzed qualitatively. Based on research findings, consumer protection for users of the FOTOYU application is an important aspect in the continuity of transactions that require guarantees of consumer rights, which include comfort and safety, clear information, compensation claims, opinions or complaints, and the right to privacy protection for uploaded images as stated in Article 4 of the Consumer Protection Law. Conversely, uploaders, in this case photographers, are certainly also entitled to security guarantees against violations of moral rights and economic rights of the creator in protecting their works, such as reproduction and adaptation of creations that may cause economic losses, as stipulated in Article 9 of Law No. 28 of 2014 on Copyright. Keywords: Legal Protection, Consumer Rights, Copyright, FOTOYU Abstrak Fenomena transaksi digital dalam aplikasi FOTOYU sebagai platform jual beli foto dan video berpotensi menimbulkan pelanggaran yang berkaitan dengan pelanggaran hak cipta, penyalahgunaan data pribadi, serta penggunaan karya tanpa izin. Kondisi ini mencerminkan adanya pelanggaran terhadap hak-hak konsumen dan hak cipta fotografer. Tujuan penelitian ini ialah untuk menganalisis apa saja bentuk pelanggaran serta bentuk perlindungan dari pelanggaran tersebut pada aplikasi FOTOYU.Penelitian ini menggunakan metode hukum normatif dengan pendekatan deskriptif. Data diperoleh melalui penelitian kepustakaan dan penerapan norma-norma hukum sesuai dengan peraturan perundang-undangan. Data yang terkumpul kemudian dianalasis secara kualitatif.Berdasarkan hasil penelitian, perlindungan konsumen terhadap pengguna aplikasi FOTOYU merupakan aspek penting dalam keberlangsungan transaksi yang memerlukan jaminan hak atas konsumen yang meliputi kenyamanan serta kemanan, informasi yang jelas, klaim ganti rugi, pendapat atau keluhan, dan hak atas perlindungan privasi pada gambar yang diunggah tercantum dalam Pasal 4 UUPK. Sebaliknya, pengunggah yang disini ialah fotografer tentunya berhak juga mendapatkan jaminan keamanan dari pelanggaran hak moral dan hak ekonomi si pencipta dalam melindungi hasil karya ciptaannya seperti penggandaan serta pengadaptasian ciptaan yang dapat menimbulkan kerugian ekonomi sesuai yang tercantum dalam pasal 9 UUHC nomor 28 tahun 2014. Kata Kunci: Perlindungan Hukum, Hak Konsumen, Hak Cipta, FOTOYU